Behaviour of doxycycline, oxytetracycline, tetracycline and flumequine during manure up-cycling for fertilizer production. (1st October 2018) - Bousek, J.; Schöpp, T.; Schwaiger, B.; Lesueur, C.; Fuchs, W.; Weissenbacher, N.
Abstract: The fate of four widely used veterinary antibiotics (doxycycline, flumequine, oxytetracycline and tetracycline) during manure upcycling was investigated at laboratory and pilot scale. The pilot was operated continuously, while the laboratory scale in batch mode. Both set-ups consisted of anaerobic digestion, ammonia stripping and a solid liquid separation step. A partial nitritation anammox process was used to treat the laboratory scale effluent. In the pilot installation, pig manure as feed, natural occurring antibiotics levels were reduced by 92% for doxycycline, 88% for flumequine, 95% for oxytetracycline and 100% for tetracycline. In the laboratory scale set-up, antibiotic free sludge was used and the four substances were spiked. The input antibiotics concentration was reduced by 85% for doxycycline, 46% for flumequine, 97% for oxytetracycline and 100% for tetracycline. In both set-ups the centrifuge cake was identified as the major emission pathway for residual antibiotics. Manure upcycling, while producing fertilizers, can be considered effective in reducing the residual antibiotic load. Highlights: High antibiotic reduction through manure up-cycling process was observed. Combination of different treatment processes is needed for high antibiotic reduction. Antibiotic highest emissions to environment were observed through centrifuge cake. Unaccustomed anaerobic digestion was inhibited at low antibiotic concentrations.